2018
DOI: 10.1007/s00268-018-4740-5
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Practices of Gynaecologists Related to Breast Cancer Screening, Detection, Treatment and Common Breast Diseases: A Study from India

Abstract: Despite the knowledge regarding risk factors, clinical signs and treatment of breast cancer and benign breast diseases was found adequate amongst the gynaecologists, this did not apply to their clinical practice. Structured and continuous training of gynaecologists is needed to improve the outcome of patients with breast diseases in terms of better management and reference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…In a survey of female students in Karachi that included 909 participants, out of whom 541 were medical students, 71% were aware of BSE, but only 33% performed it (Ahmed et al, 2018). In 2019, 30% of the gynecologists and trainees surveyed in India recommended screening mammography to their patients regularly, which is higher than but similar to our study (Singh et al, 2019). BSE was recommended by 81% of general practitioners in a study by Raza et al in 2010 in Pakistan, which was much higher than ours, partly because our population was trainees (Raza et al, 2012).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In a survey of female students in Karachi that included 909 participants, out of whom 541 were medical students, 71% were aware of BSE, but only 33% performed it (Ahmed et al, 2018). In 2019, 30% of the gynecologists and trainees surveyed in India recommended screening mammography to their patients regularly, which is higher than but similar to our study (Singh et al, 2019). BSE was recommended by 81% of general practitioners in a study by Raza et al in 2010 in Pakistan, which was much higher than ours, partly because our population was trainees (Raza et al, 2012).…”
Section: Discussionsupporting
confidence: 79%
“…Significantly higher median awareness scores were reported for females, PGRs, and surgical PGRs compared to males, HOs, and medicine PGRs. Singh et al reported better knowledge of PGRs than house officers (Singh et al, 2019). Similarly, female general practitioners were noted to recommend breast self-examination more frequently (44% vs. 7% of the males) in a previous study (Raza et al, 2012).…”
Section: Discussionmentioning
confidence: 85%
“…NICPR promotes the integration of basic, clinical, and applied research for cancer prevention and control toward the goal of achieving population-level outcomes. Previous research in the context of cancer screening suggests that providers and health care systems in India do not have sufficient knowledge, training, and resources to deliver cancer screening services (Anandani et al, 2015;Khanna et al, 2019;Singh et al, 2012Singh et al, , 2019. One of NICPR's primary activities is to support the implementation of the national cancer control plan through training of health care providers (i.e., primary care physicians, gynecologists, nurses, and community health workers) in cancer screening and community-level cancer management.…”
Section: Introductionmentioning
confidence: 99%
“…Breast nodules are a common problem in developing countries ( 16 ). Most breast nodules in women are benign ( 17 ).…”
Section: Discussionmentioning
confidence: 99%